Nanotheranostics for personalized medicine - Kim, Tae Hyung (2013)
Nanotheranostics, the integration of diagnostic and therapeutic function in one system using the benefits of nanotechnology, is extremely attractive for personalized medicine. Because treating cancer is not a one-size-fits-all scenario, it requires therapy to be adapted to the patient’s specific biomolecules. Personalized and precision medicine (PM) does just that. It identifies biomarkers to gain an understanding of the diagnosis and in turn treating the specific disorder based on the precise diagnosis. By predominantly utilizing the unique properties of nanoparticles to achieve biomarker identification and drug delivery, nanotheranostics can be applied to noninvasively discover and target image biomarkers and further deliver treatment based on the biomarker distribution. This is a large and hopeful role theranostics must fill. However, as described in this expert opinion, current nanotechnology-based theranostics systems engineered for PM applications are not yet sufficient. PM is an ever-growing field that will be a driving force for future discoveries in biomedicine, especially cancer theranostics. In this article, the authors dissect the requirements for successful nanotheranostics-based PM.